Guardians of Horsa. [5], Into the hidden world - Black, Roan (Black, Roan. Guardians of Horsa, 2024)
The Guardians, unaware of Horsa's hidden world, are thrust into a strange land with Ice Horses, Gem Horses, and moving mountains, challenging them to confront the undiscovered realm right beneath their hooves.